The relationship between reverse logistics and new product development: implications for re-collection of pharmaceutical waste from customers - Arthanarisami Kumaraguru, Hariram (2012)
The aim of this research is to understand the relationship between the reverse logistics and new product development in pharmaceutical industries. Nowadays, many are aware of the world’s environmental issues like global warming, toxic substance usage, carbon emissions, and resource scarcity has heightened over the past decades. Government all over the world, policy makers, NGGO’s and activists are advocating for going green for the betterment of our environment, and many organisations throughout the world have responded to this by applying green principles. People are not enough aware about disposing medicinal wastes. Hence, in this research, our focus is towards recollection of medicinal wastes from the customers. For collecting the data, survey from customers, set of pharmacists and discussion with city council were performed. Data collected from the above method is used for analysis and supporting this research along with the literature review. Finally, recommendations were made to improvise the recollection of used, unused and expired medicines from the customers for recycling and proper disposal.